Volume 4: Terry Jones Pipeline Technology; Ocean Space Utilization; CFD and VIV Symposium 2006
DOI: 10.1115/omae2006-92124
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Riser VIV Using Fully Three Dimensional CFD Simulations

Abstract: Fully three dimensional computational fluid dynamics (CFD) solutions are combined with structural models of a tensioned riser to predict riser vortex induced motion. The use of three dimensional CFD solutions overcomes many of the shortcomings of combining a series of strip or two dimensional simulations to calculate the fluid forces on the riser. Three dimensional vortex structures are treated correctly and straked risers and variations in angle of attack can be studied directly. The proposed method uses fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 9 publications
2
39
0
Order By: Relevance
“…Also in this fashion, S. Holmes, O.H. Oakley and Y. Constantinides [5] studied a similar case and concluded that the coarse resolution of the grid yields discrepancies on the prediction of the forces on the cylinder. The use of such a coarse spanwise spacing is usually justified by stating that the cross-flow vibrations of the risers extends the spanwise correlation length significantly and hence lower resolutions are required.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Also in this fashion, S. Holmes, O.H. Oakley and Y. Constantinides [5] studied a similar case and concluded that the coarse resolution of the grid yields discrepancies on the prediction of the forces on the cylinder. The use of such a coarse spanwise spacing is usually justified by stating that the cross-flow vibrations of the risers extends the spanwise correlation length significantly and hence lower resolutions are required.…”
Section: Introductionmentioning
confidence: 87%
“…Even though this has been proven for the spanwise length of the excited structural vibration mode (which can go to the order of the cylinder extent), the largest spanwise correlation length of the turbulent wake of the flow is below the order of the diameter. Since only very large scale structures in the spanwise direction are captured and these are much bigger than the actual largest spanwise scale of the turbulent wake, the underresolution of the wake in the axial direction leads to unphysical effects [5].…”
Section: Introductionmentioning
confidence: 99%
“…The reason that some numerical simulations of vortex-induced vibration have been failing to accurately duplicate experimental processes is mostly due to the complexity of physics involved in the real problem. In addition, the grid topology, mesh density, boundary condition, and coupling scheme between the flow governing equations and structure motion equations commonly have strong influence on the quality of numerical results (Holmes, et al, 2006). Due to calculation disability and some deficiencies of CFD software package itself, most numerical results depended on 2D vortex simulation and then integrate the hydrodynamic forces to 3D fluid domain (Yamamotoa, et al, 2004).…”
Section: Numerical Methods For Vivmentioning
confidence: 99%
“…Due to calculation disability and some deficiencies of CFD software package itself, most numerical results depended on 2D vortex simulation and then integrate the hydrodynamic forces to 3D fluid domain (Yamamotoa, et al, 2004). Some attempts to simulate vortex-induced vibration with very large aspect ratio are indeed a 2D numerical simulation (Holmes, et al, 2006).…”
Section: Numerical Methods For Vivmentioning
confidence: 99%
“…Some attempts to simulate VIV with very large aspect ratio are indeed 2D simulations (Holmes and Owen, 2006). Kim and Rheem (2009) measured the cross flow response of a cylinder under local shear flow.…”
Section: Introductionmentioning
confidence: 99%